Functional Coatings: Sputtered NiOx Films for Stabilization of p+n‐InP Photoanodes for Solar‐Driven Water Oxidation (Adv. Energy Mater. 11/2015). Issue 11 (3rd June 2015) - Sun, Ke; Kuang, Yanjin; Verlage, Erik; Brunschwig, Bruce S.; Tu, Charles W.; Lewis, Nathan S.
<x xml:space="preserve">Abstract</x> An inorganic nickel oxide coating that enables the use of small bandgap semiconductors that can efficiently absorb solar spectrum for efficient solar driven water oxidation is reported by Nathan S. Lewis and co‐workers in article number 1402276. This multifunctional coating is optically transparent, index matched for proper antireflection, catalytically active, chemically stable, and capable of protecting self‐passivating semiconductors under water oxidation conditions. Cover design drawn by Mingjun Yang, designed by Ke Sun.